1999
DOI: 10.1002/ch.154
|View full text |Cite
|
Sign up to set email alerts
|

Treating anxiety with self‐hypnosis and relaxation

Abstract: The outcome and process of treating subclinical anxiety with self‐hypnosis and relaxation were compared. Twenty individuals who presented for treatment for ‘stress, anxiety, and worry’ were assessed (for anxiety and self‐hypnotizability), exposed to a 28‐day treatment programme (which involved daily measures of outcome and process variables), and re‐assessed (for anxiety). It was found that both self‐hypnosis and relaxation alleviated anxiety pre‐ to post‐treatment. Although there was no difference in the outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…All three studies had participants practice the selfhypnosis skills more than three times following initial training. O'Neill, Barnier, and McConkey (1999) noted that participants in the self-hypnosis group exhibited a greater sense of expectation, treatment efficacy, and overall change cognitively and behaviorally, compared with participants in the relaxation group, which buttresses a case for self-hypnosis advancing self-efficacy. When treating stress, anxiety, or hypertension there is good evidence that self-hypnosis is effective both when selfhypnosis is defined as a hetero-hypnosis precursor plus audiotape-based individual sessions and when it involves multiple self-directed self-hypnosis training sessions.…”
Section: Stress Anxiety and Hypertensionmentioning
confidence: 99%
“…All three studies had participants practice the selfhypnosis skills more than three times following initial training. O'Neill, Barnier, and McConkey (1999) noted that participants in the self-hypnosis group exhibited a greater sense of expectation, treatment efficacy, and overall change cognitively and behaviorally, compared with participants in the relaxation group, which buttresses a case for self-hypnosis advancing self-efficacy. When treating stress, anxiety, or hypertension there is good evidence that self-hypnosis is effective both when selfhypnosis is defined as a hetero-hypnosis precursor plus audiotape-based individual sessions and when it involves multiple self-directed self-hypnosis training sessions.…”
Section: Stress Anxiety and Hypertensionmentioning
confidence: 99%
“…However, the hypnosis group surpassed the relaxation group on cognitive changes and perceptions of treatment efficacy [125]. Indeed, the hypnosis patients reported superior expectations of the success of therapy [125]. A closer look at the procedures revealed that the content of the instructions given to both groups were very similar.…”
Section: Other Anxiety-related Problemsmentioning
confidence: 96%
“…At a one month follow-up, both groups indicated significant improvement on the Beck Anxiety Inventory (BAI-State and Trait) but no significant difference was found between these two groups on the BAI. However, the hypnosis group surpassed the relaxation group on cognitive changes and perceptions of treatment efficacy [125]. Indeed, the hypnosis patients reported superior expectations of the success of therapy [125].…”
Section: Other Anxiety-related Problemsmentioning
confidence: 97%
See 1 more Smart Citation
“…Hypnosis is a therapeutic tool that incorporates relaxation along with other treatment components, including imagery, self-suggestion and desensitisation (O'Neill, Barnier and McConkey, 1999;Evans and Corman, 2003). O'Neill and colleagues (1999: 71) describe hypnosis as 'a state of intense relaxation and concentration, where the mind becomes detached from everyday cares and concerns.…”
Section: Introductionmentioning
confidence: 99%